Implementasi Pengembangan Media Interaktif Berbasis Website Canva untuk Meningkatkan Minat Belajar Murid TK Go Ceria Cipayung - Dessyanti Ryantina; Rodhiyah; Eva Widiyanti; Wealty Sweet Charollyn Pasaribu; Satria Wira Yudha (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to develop and test the effectiveness of Canva-based interactive learning media in increasing the learning interest of Go Ceria Cipayung Kindergarten students. The research method used is a qualitative approach with observation and interview techniques. The interactive media developed is in the form of a website that integrates animation features, interactive quizzes, and design elements that are appropriate for the age of kindergarten children. Evaluation was conducted through pre-test and post-test using learning interest scale. The results showed an increase in interest in learning, with 8 out of 10 children successfully completing the test with high scores based on observations and interviews with teachers. The findings indicate that utilizing Canva in early childhood learning can be an innovative solution to increase children's learning engagement and motivation.